DETERMINATION OF AFTERSHOCK HYPOCENTER LOCATION, 3-D SEISMIC VELOCITY STRUCTURE AND IDENTIFICATION ACTIVE FAULT OF YOGYA EARTHQUAKES (MW = 6.3) MAY 27, 2006 - Librian, Virga
Yogyakarta Special Region is one of the areas with a high level of seismic activity in Indonesia. One of the most destructive earthquakes was the earthquake on May 27, 2006 with a moment magnitude of 6.3 which was caused by the movement of an active fault on the ground. At first the Opak fault was thought to be the cause of the Yogyakarta earthquake, but from several recent studies this earthquake was not associated with the Opak fault, but there are other faults that have not been identified to the east of the Opak fault. In this study, we analyzed the waveforms of aftershocks from 16 station networks while the German Task Force for Earthquakes (GTF) was installed for 3 months from June-August 2006. The results obtained 2,170 aftershocks from the period 3 - 17 June 2006, delineated by the existence of the fault is still being debated. From the results of the horizontal and vertical tomograms, it can be seen that there is a velocity anomaly contrast that indicates the presence of the fault and is strengthened by the results of the source mechanism which shows that the fault has a strike-slip fault mechanism in a sinistral direction. The epicenter distribution at a depth of 9 km has high velocity anomalies of Vp, Vs and low Vp/Vs ratio associated with igneous intrusion (pyroclastic rock and Oligo- Miocene volcanic from the Semilir and Nglanggran Formations).